Natives perception of immigrant in Malaysia: a case study of Myanmarese Malay Muslim immigrant in Langkawi / Ahmad Ismail and Zulkafli Mansor - Ismail, Ahmad; Mansor, Zulkafli (Research Management Institute (RMI), 2011)
This article examines the natives' perception of Myanmarese Malay Muslim immigrant in Langkawi on the issues of the impact of economy, social and environment perspective by using the frequency analysis, descriptive analysis and multiple regression analysis. The study highlights on the impact of wages competitiveness in the local construction activities, disruption of small sea fishing activities and the impact of environment of the immigrant's dwelling area. The purpose of the research is to examine what are the response and perception of the community towards the existence of the Myanmarese Malay Muslim Immigrant on the issue of study highlighted. These findings confirmed to what has been discussed among the public especially concerning the wages competitiveness between immigrant and the natives. Similarly, on the independent variable of polluted dwelling surrounding their dwelling area, the results show the deep concerned of the natives regarding the polluted environment. From the analysis of the study many respondents are strongly agreed and agreed on the event that the immigrants give a threat to local security and the immigrants were immune of any legal enforcement.